Vozes do deserto autista: relatos de famílias sobre os direitos da criança com transtorno do espectro autista (TEA). - Macêdo, Antonia Gabriela Aragão de Oliveira (2023)
In Brazil, according to Law No. 12,764, autism is considered a disability and is part of Autism Spectrum Disorder (ASD). The diagnosis of ASD involves behavioral manifestations accompanied by deficits in communication and social interaction, repetitive and stereotyped behaviors. Public policies aimed at people with disabilities (PWD) are recent and limited in meeting the care needs of people with ASD and their families, taking into account all the specificities that autism presents. There is an urgent need to implement specific laws, ensuring that these people are welcomed and respected by society. In this sense, this research aimed to analyze reports from families about access to the rights of children with Autism Spectrum Disorder (ASD). This was a qualitative research that took place in a municipality in the North Zone of the Central- West hinterland of the state of Ceará. The study was carried out in services that support children with autism, with participants being family members of children with ASD aged 3 to 10 years, whose data collection was carried out through the application of a semi-structured interview consisting of questions about the daily life of children with ASD and access to fundamental rights. The information was analyzed using the Bardin framework, which uses the association of quantitative and qualitative methods to better interpret the data. The research was approved by the Research Ethics Committee of the Vale do Acaraú State University, following the principles established by Resolution 466/12, of the National Health Council. As results obtained, it was possible to note the lack of effective dissemination of knowledge about rights and benefits, barriers of discrimination and stigma, difficulties in accessing inclusive education and issues related to access to social security. The findings also highlight the importance of public policies in promoting the fundamental rights of children with ASD and supporting their families, emphasizing the need for a more comprehensive and effective approach by the government, as well as awareness and training campaigns for professionals. of health and education.